Clinical impact of sequential treatment with ALK-TKIs in patients with advanced ALK-positive non-small cell lung cancer: Results of a multicenter analysis. Issue 2 (November 2015) - Chiari, Rita; Metro, Giulio; Iacono, Daniela; Bellezza, Guido; Rebonato, Alberto; Dubini, Alessandra; Sperduti, Isabella; Bennati, Chiara; Paglialunga, Luca; Burgio, Marco Angelo; Baglivo, Sara; Giusti, Raffaele; et al.
Highlights: The outcome of 69 ALK -positive NSCLCs treated with a 1st ALK-TKI was investigated. Upon failure of a 1st ALK-TKI, 22 patients received a 2nd ALK-TKI. 7 and 8 NSCLCs received the same ALK-TKI and other systemic therapies, respectively. ORR and PFS on a 2nd ALK-TKI were 86.4% and 7 months, respectively. Post-progression survival favored both the 2nd ALK-TKI and beyond progression group. Abstract: Objectives: Anaplastic lymphoma kinase ( ALK )-positive non-small cell lung cancer (NSCLC) is sensitive to treatment with an ALK-tyrosine kinase inhibitor (-TKI). However, the benefit of sequential treatment with a 2nd ALK-TKI in patients who fail a 1st ALK-TKI has been poorly addressed. Materials and methods: We collected the data of 69 advanced ALK -positive NSCLCs who were treated with one or more ALK-TKIs at three Italian institutions. The clinical outcome of treatment with an ALK-TKI and the patterns of treatment upon failing a 1st ALK-TKI were recorded. Results: Objective response rate (ORR) and median progression-free survival (PFS) on a 1st ALK-TKI (mostly crizotinib) were 60.9% and 12 months, respectively. Of the 50 patients who progressed on a 1st ALK-TKI, 22 were further treated with a 2nd ALK-TKI (either ceritinib or alectinib), for whom an ORR of 86.4% and median PFS of 7 months, respectively, were reported. Conversely, 13 patients underwent rapid clinical/radiographic disease progression leading to death shortly after discontinuation of the 1st ALK-TKI, 7 patients were managed with a 1st ALK-TKI beyond progression, and 8 patients transitioned to other systemic treatments (mostly chemotherapy). Post-progression survival (PPS) significantly favored the 22 patients who were sequentially treated with a 2nd ALK-TKI over those who transitioned to other systemic treatments ( P = 0.03), but not versus those who were treated with a 1st ALK-TKI beyond progression ( P = 0.89). Conclusion: Sequential treatment with a 2nd ALK-TKI is effective in patients who fail a 1st ALK-TKI. Continuous ALK-inhibition upon failing a 1st ALK-TKI may be associated with improved clinical outcome.